MENCIPTAKAN RUANG UNTUK DIRI SENDIRI: MENGGALI KESEHATAN MENTAL MELALUI SELF-LOVE - Zainab, Syarifah; Aridhona, Julia; Dilariza, Sarah (Jurnal Abdimas Bina Bangsa, 2024)
The life of the Islamic boarding school causes many phenomena related to psychology, especially in adolescents. The psychological well-being of adolescents who study in Islamic boarding schools is more complex because they are required to be independent and must adapt quickly. The purpose of this Community Service is to increase insight and understanding of themselves and improve adolescent skills in understanding themselves so that it has an impact on improving adolescent mental health. The methods used are providing training (workshops), pretests, posttests, and screening on adolescent mental health. The participants of this training were 36 students of the Baitul Arqam Muhammadiyah Sibreh Islamic Boarding School, Aceh Besar. This training is expected to help students improve their self-understanding skills through self-love. From this understanding, students can improve their mental health as students who are required to have many tasks in their daily lives in the Islamic boarding school environment. From the results of the pretest and posttest, it was found that there was no increase in understanding of self-love if the training was not carried out periodically. Meanwhile, from the results of the mental health screening, there were several subjects who needed the help of psychologists to help the subjects solve mental health problems. The output of this community service is in the form of mapping the health levels of adolescent students at Islamic boarding schools and publication of scientific journals